2007
DOI: 10.1002/mrd.20731
|View full text |Cite
|
Sign up to set email alerts
|

Birth of correctly genotyped calves after multiplex marker detection from bovine embryo microblade biopsies

Abstract: We report a method for multiplex genotyping of bovine embryo microblade biopsies. We have tested the reliability of the method and the viability of the embryos in vitro and in vivo. Two polymorphic gene markers (GHR F279Y and PRLR S18N) associated with milk production traits and one marker for sex diagnosis (ZFX/ZFY) were genotyped simultaneously with a method that combines nested PCR and allelic discrimination. To test the accuracy of genotyping, in the first experiment the genotypes of 134 biopsies from in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…The technique expands to include other DNA markers associated with valuable production traits. Nowadays it can be used for multiplex genotyping of bovine embryos (Peippo et al, 2007;Hirayama et al, 2008;Alonso et al, 2009) and for genetic testing for hereditary diseases (Hirayama et al, 2004;Ipate et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The technique expands to include other DNA markers associated with valuable production traits. Nowadays it can be used for multiplex genotyping of bovine embryos (Peippo et al, 2007;Hirayama et al, 2008;Alonso et al, 2009) and for genetic testing for hereditary diseases (Hirayama et al, 2004;Ipate et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Results reported initially in the literature for ruminants were based on typing for a limited number of markers [48]. Field studies with in vivo produced, biopsied embryos (either fresh or frozen) have shown that pregnancy rates following transfer on-farm were compatible with field use [34] (Table 2).…”
Section: Embryo Typingmentioning
confidence: 99%
“…Cela ouvre la voie pour développer de nouvelles stratégies basées sur le diagnostic pré-implantatoire, applicable dès la première semaine de développement, dans le cadre d'opérations de collectes d'embryons. Les avantages du génotypage de l'embryon ont été rapportés dès que la sélection assistée par marqueurs (SAM), basée sur un nombre limité de marqueurs micro satellites a été utilisée, en raison de l'estimation simultanée de plusieurs caractères dès un stade précoce de développement (Peippo et al, 2007). Les avantages vis-à-vis du progrès géné-tique potentiel sont encore plus importants avec l'utilisation d'un grand nombre de marqueurs SNP (Humblot et al, 2010).…”
Section: Diagnostic Pré-implantatoire à Partir De Cellules Embryonnairesunclassified